Віктор Петров: «скіфський сюжет» інтелектуальної біографії - Андрєєв, В.М. (Український історичний журнал, 2010)
2009 р. виповнилося 115 років від дня народження та 40 років із дня
смерті В.Петрова. Цього українського інтелектуала з надзвичайною ерудицією й широтою наукових зацікавлень і поглядів, безумовно, можна назвати визначною постаттю гуманітарної думки ХХ ст. – історик, археолог, філолог, філософ і талановитий письменник із кола неокласиків.
Проте він залишається маловідомим не тільки у світовому науковому
просторі, а й на Батьківщині. Про В.Петрова написано мало, а його багатогранна інтелектуальна спадщина, як і «скіфська складова» творчості вченого, ще й досі залишаються поза увагою дослідників. In 2009 one hundred and fifteen years have passed since V.Petrov’s
birthday and forty years from his death. About this Ukrainian intellectual,
who was a person of outstanding erudition and broad range of scientific
interests, we can say that he was eminent person of the humanities in the
20th century. He was known as a historian, an archeologist, a philologist, a
philosopher and talented writer from the neoclassic circle. But nowadays he
is still unknown not only in western scientific world, but in his native country,
too; there is no any generalizing monograph and his many-sided intellectual
heritage is forgotten. «Scythian constituent» of Petrov’s work is not
exception to the rule; it still remains without attention of researchers. This
article is devoted to analysis of Petrov’s work in field of scythologia.